2014
DOI: 10.1093/jxb/eru041
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen cytosolic glutamine synthetase genes identified in the Brassica napus L. genome are differentially regulated depending on nitrogen regimes and leaf senescence

Abstract: Summary BnaGLN1 coding sequences and expression profiles in response to nitrogen availability and ageing are essentially conserved compared with A. thaliana, suggesting that the roles of GLN1 families are conserved among the Brassiceae tribe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…This was supported by Miro et al (2010), who found B. napus nitrate transporters, and other genes implicated in nitrate regulation, underlying N-responsive QTLs. Orsel et al (2014) found 16 BnaGLN1 genes coding for cytosolic glutamine synthase in rapeseed. In addition, two homoeologous genes (BnSAG12-1 and BnSAG12-2) coding for SAG12, a cysteine protease implicated in N remobilization, were observed to reach maximum expression levels at early stages of senescence (Noh and Amasino 1999).…”
Section: Genetic Control Of Traits Related To Nitrogen Utilization Efmentioning
confidence: 99%
See 2 more Smart Citations
“…This was supported by Miro et al (2010), who found B. napus nitrate transporters, and other genes implicated in nitrate regulation, underlying N-responsive QTLs. Orsel et al (2014) found 16 BnaGLN1 genes coding for cytosolic glutamine synthase in rapeseed. In addition, two homoeologous genes (BnSAG12-1 and BnSAG12-2) coding for SAG12, a cysteine protease implicated in N remobilization, were observed to reach maximum expression levels at early stages of senescence (Noh and Amasino 1999).…”
Section: Genetic Control Of Traits Related To Nitrogen Utilization Efmentioning
confidence: 99%
“…The polyploid nature of B. napus implies the duplication of genes involved in NUE traits within the genome and their organization into large multigene families, with possible variations in spatiotemporal gene expression patterns. For instance, the 16 BnaGLN1 genes detected by Orsel et al (2014) were organized into five distinct families that were differentially modulated according to N availability. Two gene families were upregulated under low N conditions and during leaf senescence, while one family was upregulated under high N conditions.…”
Section: Genetic Control Of Traits Related To Nitrogen Utilization Efmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to environmental constraints on agriculture, two targets are of crucial interest. In WOSR, nitrogen fertilization, a non renewable input, represents the major operational cost for growers (Orsel et al, 2014). The improvement of nitrogen use efficiency (NUE) is therefore a key target as far as WOSR yield increase or stability remains the overall objective of crop production.…”
Section: Yield: "Produce More With Less"?mentioning
confidence: 99%
“…However, in that study, the range of N stress was relatively limited. Research on NUE improvement in WOSR greatly benefited from studies on the model crop Arabidopsis thaliana (Chardon et al, 2012, Masclaux-Daubresse et al, 2010, Orsel et al, 2014, pointing out the need of more integrated translational research, i.e. from model crops to cultivated crops.…”
Section: Yield: "Produce More With Less"?mentioning
confidence: 99%